Studio Culture Now - Sinclair, Mark (London : Unit Editions, 2020)
Atelier Dyakova ; Champions Design ; Civilization ; Design by Toko ; D I A ; ÉricandMarie ; Formist ; Google Design ; GUNMAS / Or Type ; Hansje van Halem ; Helmo ; Hey Studio ; Hubertus Design ; Jade Purple Brown ; Julia ; MorcosKey ; My Name is Wendy ; Neubau ; Office of Craig ; OK-RM ; Parámetro Studio ; Peepshow ; ps.2 arquitetura + design ; Regular Practice ; Sara De Bondt studio ; Sarah Boris Studio ; Studio Rejane Dal Bello ; Vrints-Kolsteren ; WeShouldDoItAll ; YesYesNo
Studio Culture Now features in-depth interviews with a host of leading design studios. The interviewees share their experiences, insights, fears and joys, and reveal how they deal with the fundamentals and aspirations of studio life. Candid and generous, these extensive Q&As form a blueprint for anyone planning a studio practice, or anyone struggling with maintaining one. Topics covered include: getting jobs, working with clients, balancing creativity with profitability, accounting, hiring, promotion, wellbeing, and much more. The interviews, mostly conducted in the past few months, also reveal how studios are adapting to the changes brought about by the coronavirus pandemic.(from publisher)
boek